Solvent/Ligand-Controlled Switchable C3 or C7 C–H Arylations of 1-Methyl-4-nitro-1H-indazole - Boujdi, Khalid; El Brahmi, Nabil; Collet, Sylvain; Dubreuil, Didier; Mathé-Allainmat, Monique; Akssira, Mohamed; Guillaumet, Gérald; Lebreton, Jacques; El Kazzouli, Saïd (Synthesis, 2022)
A new solvent/ligand-controlled switchable C–H arylation of 1-methyl-4-nitro-1H-indazole catalyzed by Pd(OAc)2 was achieved. A bidentate ligand in DMA promoted the activation at C7 position, while a phosphine ligand in H2O oriented the arylation at C3 position. The C3 and C7 arylation products were obtained in moderate to good yields and with high regioselectivity.
Keywords: heteroarenes; indazole; C–H activation; C–H arylation; regioselectivity